The Role of Job Stress in Mediating the Influence of Work-Life Balance and Workload on Employee Job Satisfaction - Muzti, Mohd Farhan; Mardiana, Tri (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
The type of research that researchers conduct is quantitative research which aims to determine the effect of Work Life Balance and Workload on Employee Job Satisfaction with Job Stress as a mediating variable. The population used in this study were 210 employees of the production department of PT Margaria Group Yogyakarta. The sampling technique was carried out using probability sampling with the method of Issac and Michael so that a sample of 136 employees was obtained with the majority being female as many as 82 people, the majority aged 20-25 as many as 61 people, with the majority married status as many as 105 people, the majority of high school / high school education as many as 84 people, the majority of 5-10 years of service as many as 63 people. Data collection was carried out using a questionnaire. The analysis technique used in this research is path analysis. The results of this study concluded that Work Life Balance has a positive and significant effect on Employee Job Satisfaction and Workload has a positive and significant effect on Employee Job Satisfaction. Work Life Balance and Workload have a significant effect on Employee Job Satisfaction indirectly through Job Stress as a mediating variable.